FACTORS AFFECTING THE ANXIETY LEVEL OF PRE-SURGICAL PATIENTS IN HOSPITAL - Maulidia Khairani; Siska Mayang Sari; Rani Lisa Indra (Jurnal Riset Kesehatan, 2023)
A surgical procedure may induce psychological reactions in patients, including pre-surgical anxiety. Pre-surgical anxiety can influence the surgical process and patients’ health status after the surgery. Mild, moderate, and severe anxiety are some of the psychological responses to surgical procedures. Patients' anxiety before surgery is affected by internal and external factors. 30 respondents had the most anxiety levels of moderate preoperative patients, with 12 respondents (40%) and 18 respondents (60%) having surgical with mild preoperative anxiety levels. There were 25 respondents with less knowledge. There were 16 respondents (64%) with mild anxiety levels and 9 (36%) with moderate anxiety levels. 55 respondents with high family support, there were 48 respondents (87.3%) with moderate anxiety levels, there were 5 respondents (7.4%) with severe anxiety levels and 2 respondents (3.6%) with mild anxiety levels. The exact cause of anxiety is unknown, but it is thought to factor in experience, knowledge, and family support or RSUD Arifin Achmad, Riau Province. The study aims to describe factors that influence anxiety in patients’ pre-operation. The research instrument was a questionnaire through validity and reliability tests. Univariate and bivariate analyses were applied. The research instrument was a questionnaire through validity and reliability tests. The research showed no significant correlations between experiences, knowledge, and family support with the patients’ anxiety (p-value0.05). It was suggested that the hospital should concern with factors correlated with pre-surgical patients' anxiety and increase the quality of nursing care.